Activities of the wintering party at Asuka Station by the 29th Japanese Antarctic Research Expedition in 1988-1989 - Keizo Yanai (National Institute of Polar Research, 1990)
The wintering activities at Asuka Station by the 29th Japanese Antarctic Research Expedition (JARE-29) are reported. The winter party at Asuka Station, (the Asuka party), consisted of 10 persons including four scientists. On December 28,1987,the Asuka party took over Asuka Station which was started by JARE-28 in February 1987,then continuously maintained the station during the wintering. The station was succeeded by JARE-30 on December 22,1988. The main scientific program of the Asuka party is the search for Antarctic meteorites on the bare ice around the Sor Rondane Mountains. Other programs comprised the meteorological surveys, studies of upper atmosphere physics, glaciological survey, medical-biological studies, and logistic survey of the housing at Asuka Station. A systematic search for Antarctic meteorites was carried out five times, between January 1988 and January 1989,amounting to about 150 days. More than 2000 meteorites, about 400 kg in weight, were collected from three main areas around the mountains. The other programs were also carried out successfully during the wintering.